Temporal evolution of mid-tropospheric CO2 over the Indian Ocean. (15th July 2021) - Peter, R.; Kuttippurath, J.; Chakraborty, Kunal; Sunanda, N.
Abstract: The rapid increase in carbon dioxide (CO2 ) in the atmosphere due to anthropogenic activities aids global warming that demands immediate attention and policy actions. The changes in weather patterns, such as winds, temperature and precipitation, leading to floods and droughts are linked to the increasing greenhouse gases including CO₂. This situation warrants close and continuous monitoring of atmospheric CO2 . Here, the mid-tropospheric CO2 from Atmospheric Infrared Sounder (AIRS) is analysed for the past 14 years over Indian Ocean. The northern hemisphere has a higher CO2 concentration than the southern hemisphere, as most of the landmasses with significant CO2 sources are present in the former region. Seasonal variations show the highest CO2 concentration over the north Indian Ocean (NIO) during MAM (March, April and May), about 388.55 ppm, and lowest during ON (October and November), about 386.92 ppm. In contrast, the south Indian Ocean shows the highest, but the magnitude is smaller than that over NIO, during December, January and February. Arabian Sea (AS) exhibits smaller CO2 concentrations compared to that over Bay of Bengal (BoB). However, AS shows the highest trend of 2.13 ppm/year during the post-monsoon season (ON). The seasonal correlation analysis of the temperature at 10 m and sea surface temperature against mid-tropospheric CO2 shows a higher positive correlation for BoB. These analyses, therefore, provide a detailed understanding of the basin-wide seasonal and inter-annual trends of mid-tropospheric CO2 over Indian Ocean. Graphical abstract: Image 1 Highlights: A long-term analysis of mid-tropospheric CO2 over the Indian Ocean. The CO2 trends are higher in Arabian Sea (2.13 ppm/yr) than that in Bay of Bengal. The CO2 has a correlation of 0.44 with surface temperature in pre-monsoon. Distinct changes during the ENSO and IOD events.